Ethics in Youth Work: A Retreat From Politics? (Concept: The Journal of Contemporary Community Education Practice Theory, 2015)
In the articles that follow, both writers make arguments inviting us to think about why this interest has arisen, and how it might be understood. Tony Taylor argues from an activist professional perspective for the primacy of politics as the lens through which to understand the issue. Approaching the problem as a moral philosopher, Sarah Banks offers analysis and commentary rather than direct counterargument, suggesting that: ‘The challenge is not to divert attention from ethics to politics, but rather to promote a radical ethics that also acknowledges the connection with politics.’